Symbols and Typical Expressions in Maritime English - I Wy Dirgeyasa (Universitas Negeri Medan, 2016)
At present time, millions of people work in the maritime field worldwide. Of the millions people, they come from different countries with a diverse background with different level of English proficiencies which they bring from their home countries. That is why; the mastery of standard maritime communication system is a must. To be able to communicate correctly and properly in the Maritime World and industry, the ships’ crews must understand and master the typical features of Maritime English. This paper focuses and reviews an account of the typical features of Maritime English communication in terms of 1) Maritime English spelling system in communication, 2) maritime symbols and their meanings, and 3) typical expressions. Keywords: spelling system, symbols, typical expressions